Human macrophages stimulate expression of inflammatory mediators in adipocytes; effects of second-generation antipsychotics and glucocorticoids on cellular cross-talk. (March 2021) - Sarsenbayeva, Assel; Dipta, Priya; Lundqvist, Martin; Almby, Kristina E.; Tirosh, Boaz; Di Nunzio, Giada; Eriksson, Jan W.; Pereira, Maria J.
Abstract: Objective: Adipose tissue inflammation and distorted macrophage-adipocyte communication are positively associated with metabolic disturbances. Some pharmacological agents, such as second-generation antipsychotics (SGAs) and synthetic glucocorticoid (GC) dexamethasone, tend to induce adverse metabolic side effects and the underlying mechanisms are not fully understood. Our work aimed to study whether SGAs and dexamethasone affect macrophage phenotype and macrophage-adipocyte communication on gene expression level. We selected the model involving THP-1-derived macrophages, polarized into M0, M1, and M2 phenotypes, and primary human mature subcutaneous adipocytes. Methods: Abdominal subcutaneous adipose tissue needle biopsies were obtained from 6 healthy subjects (4F/2M; age: 22–64 yr; BMI: 21.7–27.6 kg/m2) followed by isolation of mature adipocytes. THP-1-human monocytic cell line was used for the study. THP-1 monocytes were differentiated and polarized into M0 (naïve), M1 (classically activated), and M2 (alternatively activated) macrophages. During and after polarization the macrophages were treated for 24 h without (control) or with therapeutic and supra-therapeutic concentrations of olanzapine (0.2 µM and 2.0 µM), aripiprazole (1.0 µM and 10 µM) and its active metabolite dehydroaripiprazole (0.4 µM and 4.0 µM). Isolated mature human adipocytes were co-incubated with THP-1-derived polarized macrophages pre-treated with SGAs after their polarization. Adipocytes and macrophages were collected before and after co-culture for mRNA expression analysis of genes involved in inflammation. Results: Co-incubation of mature human adipocytes with human macrophages, regardless of polarization, resulted in a marked induction of pro-inflammatory cytokines in adipocytes, including IL1B, IL6, TNFA, and IL10 . Remarkably, it did not affect the expression of adipokines and genes involved in the regulation of energy, lipid, and glucose metabolism in adipocytes. Dexamethasone markedly reduced gene expression of pro-inflammatory cytokines in macrophages and prevented macrophage-induced inflammatory response in adipocytes. In contrast, SGAs did not affect macrophage-adipocyte communication and had a minute anti-inflammatory effect in macrophages at supra-therapeutic concentrations. Interestingly, the adipocytes co-incubated with M1 macrophages pre-treated with dexamethasone and SGAs particularly the supra-therapeutic concentration of olanzapine, reduced expression of LPL, LIPE, AKT1, and SLC2A4, suggesting that the expression of metabolic genes in adipocytes was dependent on the presence of pro-inflammatory M1 macrophages. Conclusion: Together, these data suggest that macrophages induce expression of pro-inflammatory genes in human subcutaneous adipocytes without affecting the expression of adipokines or genes involved in energy regulation. Furthermore, our findings demonstrated that SGAs and dexamethasone had a mild effect on macrophage-adipocyte communication in M1 macrophage phenotype. Highlights: Macrophages induce pro-inflammatory cytokine gene expression in isolated mature adipocytes. Macrophages do not change the expression of adipokines or genes involved in energy regulation. SGAs and dexamethasone had anti-inflammatory effect in macrophages. SGAs had no significant effect on macrophage-adipocyte communication. Dexamethasone prevented upregulation of pro-inflammatory genes in adipocytes.